When Text Meets Context: Sociological and Hadith Perspectives on Interfaith Marriage in Indonesian Muslim Society - Diki Achmad Zulkarnaen; Wahyudin Darmalaksana; Reza Pahlevi Dalimunthe; Engkos Kosasih; Rizzaldy Satria Wiwaha (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to analyze the perspectives of sociologists and hadith scholars on the practice of interfaith marriage in Indonesia, as well as to evaluate the social and religious impacts of the interaction between these two perspectives within the context of a Muslim society that is plural yet tends to be legally conservative in religious matters. This research is significant because interfaith marriage frequently generates dissonance between the constitutional rights of citizens and shar‘i norms, while also serving as a site of value negotiation amid the increasing intensity of interreligious interactions. The method employed is descriptive qualitative research using a sociology of hadith approach, combining an analysis of both classical and contemporary hadith literature with theories of the sociology of religion. Data were collected through a literature review encompassing hadith collections, exegetical and jurisprudential works of scholars, academic publications, as well as legal and policy reports. Data analysis was conducted using thematic content analysis, hermeneutics, and comparative analysis in order to identify points of convergence and divergence between sociological and normative-hadith perspectives. The findings reveal that the sociological perspective positions interfaith marriage as a complex social phenomenon—closely related to social integration, identity negotiation, and value conflicts—whereas the hadith perspective emphasizes the preservation of faith, household stability, and protection of lineage, with only limited and conditional space for permissibility. The interaction between these perspectives produces multidimensional effects, ranging from social resistance and the marginalization of couples to the creation of interfaith dialogue spaces within inclusive urban communities. The implications of this research lie in the need for policies that bridge religious norms and positive law, including through interfaith dialogue, public education, and pastoral guidance for interfaith families. The originality of this study lies in its integration of sociological analysis with hadith studies to contextualize the issue of interfaith marriage, offering an analytical framework that connects religious texts with socio-historical dynamics, and providing practical contributions for policy development in plural societies.